Analysis of Beginning Reading and Writing Media Needs Based on Interactive Multimedia - Prabawati Nurhabibah; Subyantoro Subyantoro; Rahayu Pristiwati; Haryadi Haryadi (International Conference on Science, Education, and Technology, 2023)
The issue of early reading and writing in Indonesia has attracted the attention of many researchers in the country. However, until now, there has been no research that addresses the root of this problem. Teachers and parents certainly always hope that their children can develop their literacy skills optimally so that they can succeed in the learning process at school. However, there is no media that effectively supports the efforts of teachers and parents. Therefore, this research aims to analyze the needs of teachers and parents in terms of early reading and writing activities for children, both at school and at home, through the development of interactive multimedia. The methods used in this research were questionnaires and interviews conducted with 28 elementary school teachers and 15 parents of students. The results of the research show the importance of first introducing alphabet recognition activities (A-Z). In addition, attention should be paid to the use of paper (thickness and color). The variation of letter types and sizes used in media production should also be considered, including incorporating many pictures and animations, providing easily understandable, clear, and organized content, utilizing technology and interactive multimedia. With these findings, it is hoped that there will be the development of interactive multimedia that includes these activities to be used in early literacy activities for elementary school-aged children.